Cross-Modal Musical Expectancy in Complex Sound Music: A Grounded Theory - Correa, Juan Pablo (Journal of cognition, 2023)
Expectancy is a core mechanism for constructing affective and cognitive experiences of music. However, research on musical expectations has been largely founded upon the perception of tonal music. Therefore, it is still to be determined how this mechanism explains the cognition of sound-based acoustic and electroacoustic music, such as complex sound music (CSM). Additionally, the dominant methodologies have consisted of well-controlled experimental designs with low ecological validity that have overlooked the listening experience as described by the listeners. This paper presents results concerning musical expectancy from a qualitative research project that investigated the listening experiences of 15 participants accustomed to CSM listening. Corbin and Strauss’ (2015) grounded theory was used to triangulate data from interviews along with musical analyses of the pieces chosen by the participants to describe their listening experiences. Cross-modal musical expectancy (CMME) emerged from the data as a subcategory that explained prediction through the interaction of multimodal elements beyond just the acoustic properties of music. The results led to hypothesise that multimodal information coming from sounds, performance gestures, and indexical, iconic, and conceptual associations re-enact cross-modal schemata and episodic memories where real and imagined sounds, objects, actions, and narratives interrelate to give rise to CMME processes. This construct emphasises the effect of CSM’s subversive acoustic features and performance practices on the listening experience. Further, it reveals the multiplicity of factors involved in musical expectancy, such as cultural values, subjective musical and non-musical experiences, music structure, listening situation, and psychological mechanisms. Following these ideas, CMME is conceived as a grounded cognition process.